2013
DOI: 10.1111/j.1743-498x.2012.00591.x
|View full text |Cite
|
Sign up to set email alerts
|

Peer observation and feedback of resident teaching

Abstract: Peer observation and feedback of resident teaching during work rounds is feasible and rewarding for the residents involved. Comfort with regards to being observed by peers, with receiving feedback from peers and with giving feedback to peers significantly increased after the study. Most residents reported changes in their teaching behaviour resulting from feedback. Residents felt that observing a peer teach on work rounds was one of the most useful activities to improve their own teaching on work rounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 9 publications
1
27
0
Order By: Relevance
“…Near‐peer teaching programmes are widely described in undergraduate medical education literature, and considering the benefits described in this setting NPT could enhance the training of junior doctors in a variety of ways. There are limited reports of NPT in postgraduate medical training; however, no articles have evaluated its use for the delivery of regular formalised teaching to UK junior doctors. We have developed an NPT programme in which regular FY2 teaching was delivered exclusively by more senior CMT colleagues, and have presented the results of our pilot study.…”
Section: Discussionmentioning
confidence: 99%
“…Near‐peer teaching programmes are widely described in undergraduate medical education literature, and considering the benefits described in this setting NPT could enhance the training of junior doctors in a variety of ways. There are limited reports of NPT in postgraduate medical training; however, no articles have evaluated its use for the delivery of regular formalised teaching to UK junior doctors. We have developed an NPT programme in which regular FY2 teaching was delivered exclusively by more senior CMT colleagues, and have presented the results of our pilot study.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the title and abstract review, we fully reviewed 14 additional articles on RaT of which 13 were relevant (Butani et al, 2013;Donato and Harris, 2013;Donovan, 2011;Keller et al, 2012;Lachman, Christensen, and Pawlina, 2013;Lakshmanan et al, 2014;Patocka, Meyers, and Delaney, 2011;Peyre et al, 2011;Ricciotti et al, 2012;Smith and Kohlwes, 2011;Snydman et al, 2013;Wachtel, Greenberg et al, 2013;Yuan et al, 2014). Current trends in the literature are that 1) RaT programs vary in content and design, with mostly discipline-specific, one-off deliveries; 2) program evaluations are not conducted aside from some assessments of resident teaching; and 3) a learner-centered approach should be incorporated into program development and implementation (Jarvis-Selinger et al, 2011).…”
Section: Literature Searchmentioning
confidence: 99%
“…14 Considering that resident doctors play an important role in the education of medical students, a survey-based observational study revealed that peer observation and feedback of residents' teaching during work rounds is not only feasible but also rewarding for the involved residents and thus should be encouraged. 15 Moving a step further, the findings of another study revealed that the provision of feedback by faculty staff to resident doctors after observing resident-patient interactions is a complex and dynamic process. In this feedback-giving exercise, there is definite scope for the adoption of a potential newer approach that can assist in enhancing the effectiveness of the feedback of faculty members and thus, ultimately, in faculty development.…”
Section: Bridging the Gapmentioning
confidence: 99%